The geography of the world economy / Paul Knox, John Agnew and Linda McCarthy. - Knox, Paul L.; Agnew, John A.; McCarthy, Linda (London : Hodder Education, 2008)
The Geography of the World Economy provides an in-depth introduction to the globalization of the world economy and discusses local, regional, national and global economic development over the course of history. This new edition is fully revised and in colour.
Includes bibliographical references and index.
Keywords: Economic geography; Economic history